2021
DOI: 10.3122/jabfm.2021.03.200307
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Diabetes Clinic Improves Clinical and Behavioral Outcomes in a Primary Care Setting

Abstract: The percentage of adults achieving hemoglobin A1c goals less than 7% remains a challenge. The study objective was to evaluate effects of a multidisciplinary approach on behavioral outcomes and mean change in A1c in immediate start (intervention) versus 6-month delay (control) groups at 6 months. The study assessed 111 patients recruited from a safety-net primary care clinic with a pharmacist-led multidisciplinary team and found that the intervention improved mean A1c outcomes for patients with type 2 diabetes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Various health care professionals working with people with diabetes may contribute to psychosocial care in different ways based on training, experience, need, and availability (313,326,327). Ideally, qualified mental health professionals with specialized training and experience in diabetes should be integrated with or provide collaborative care as part of diabetes care teams (328)(329)(330)(331), or referrals for in-depth assessment and treatment for psychosocial concerns should be made to such mental health professionals when indicated (314,332,333). A systematic review and meta-analysis showed that psychosocial interventions modestly but significantly improved A1C (standardized mean difference -0.29%) and mental health outcomes (334).…”
Section: Supporting Positive Health Behaviorsmentioning
confidence: 99%
“…Various health care professionals working with people with diabetes may contribute to psychosocial care in different ways based on training, experience, need, and availability (313,326,327). Ideally, qualified mental health professionals with specialized training and experience in diabetes should be integrated with or provide collaborative care as part of diabetes care teams (328)(329)(330)(331), or referrals for in-depth assessment and treatment for psychosocial concerns should be made to such mental health professionals when indicated (314,332,333). A systematic review and meta-analysis showed that psychosocial interventions modestly but significantly improved A1C (standardized mean difference -0.29%) and mental health outcomes (334).…”
Section: Supporting Positive Health Behaviorsmentioning
confidence: 99%
“…A total of 1468 articles were identified (n = 1456 from databases; n = 12 from manual search of references) of which 331 were duplicates and 2 articles were not accessible by the authors, leaving 1125 articles screened for eligibility (Figure 1). Thirty articles were reviewed after 1095 articles were excluded 11–40 …”
Section: Resultsmentioning
confidence: 99%
“…Other outcomes were body mass index, emergency department visits, hospitalizations, adverse events from drug use, and direct medical costs. Among the 30 studies, 10 (33.3%) of them evaluated PROs, with medication adherence, self‐efficacy and self‐care being most commonly evaluated (n = 5, 50.0%), followed by diabetes‐ and medication‐related knowledge (n = 4, 40.0%) 11–13,16,20,26,29,34,38,39 . Self‐efficacy refers to one's confidence and ability to self‐manage diabetes, including diet, physical activities, and treatment 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations